Effect of different drying methods on the taste and volatile compounds, sensory characteristics of Takifugu obscurus - Youyou Li; Shui Jiang; Yiwen Zhu; Wenzheng Shi; Yin Zhang; Yuan Liu (Food Science and Human Wellness)
Pufferfish is prone to deterioration due to abundant nutrients and high moisture content. Drying technology can extend the shelf life and enhance the flavor quality of aquatic products. The study investigated the effect of hot air drying (HAD), microwave vacuum drying (MVD) and hot air assisted radio frequency drying (HARFD) on the taste and volatile profiles of Takifugu obscurus. Different drying methods had significant influence on the color, rehydration, 5'-nucleotides, free amino acids and volatile components (P < 0.05). The results showed that HAD and HARFD could promote the flavor of T. obscurus by producing higher equivalent umami concentration (EUC) values, which were about two times of MVD group, and more pronounced pleasant odor according to sensory analysis. HAD is more appropriate for industrial application than HARFD and MVD considering the economic benefits. This study could provide a reference for the industrial application of drying T. obscurus.